TBX1 Functions as a Tumor Activator in Prostate Cancer by Promoting Ribosome RNA Gene Transcription - Cui, Jie; Zhang, Yamin; Ren, Xiaoyue; Jin, Lei; Zhang, Hongyi (Frontiers in Oncology, 2021)
TBX1 belongs to an evolutionarily conserved family of transcription factors involved in organ development. TBX1 has been reported to have a hypermethylated cytosine guanine dinucleotide island around its second exon, which was related to prostate cancer (PCa) progression. However, the role and exact mechanism of TBX1 in PCa remains unknown. Using human prostate samples, online data mining and multiple in vitro and in vivo models, we examined the biological role and underlying mechanisms of TBX1 in PCa. TBX1 was highly expressed in PCa tissues, and high TBX1 expression was positively associated with Gleason score, pathological tumour stage, pathological lymph node stage, extraprostatic extension and disease/progression-free survival. In vitro and in vivo data demonstrated that TBX1 silencing inhibits PCa cell proliferation and colony formation and increases the cell population at the G0/G1 phase. The exogenous expression of TBX1 rescued these phenotypes. Mechanistically, TBX1 silencing suppressed the expression of 45S ribosomal RNA (rRNA), which was rescued by the exogenous expression of TBX1. TBX1 silencing inhibited the monomethylation of histone 3 lysine 4 (H3K4me1) binding with the non-coding intergenic spacer (IGS) regions of ribosomal DNA (rDNA) and the recruitment of upstream binding factor to the promoter and IGS regions of rDNA. The drug-induced enhancement of H3K4me1 counteracted the effect of TBX1 silencing. These findings indicate that TBX1 exerts its tumour activator function in PCa cells via epigenetic control, thereby promoting rRNA gene transcription. Thus, TBX1 may represent a prognostic biomarker and therapeutic target for PCa patients.